Isolated Bilateral Pinna Swelling: A Rare Initial Presentation of Leprosy - Mohd Yusuf, Salma; Ismail, Ilham Ameera; Abdul Hamid, Rumihati; Jamil, Nur Adliah; Md Yasin, Mazapuspavina (Open Access Macedonian Journal of Medical Sciences, 2019)
BACKGROUND: Leprosy or Hansen disease is a chronic infectious disease that causes social stigma due to its deforming bodily appearance and physical disability. It has a wide spectrum of presentation affecting diagnosis. CASE REPORT: A 21-year-old man who presented with chronic isolated bilateral pinna swelling as a result of leprosy is reported. The bilateral pinna swelling started as multiple shiny papules with an erythematous background and progressively became hyperpigmented and lobular over two years. This rare presentation of leprosy poses initial diagnostic difficulties, leading to misdiagnoses by various health care professionals. Diagnoses ascribed include eczema, insect bite and perichondritis. A suspicion of leprosy was raised when hyperaesthetic hypopigmentation of skin started to appear on the body after two years, with worsening of the pinna swellings. This was confirmed by identification of Mycobacterium leprae in slit skin smear test and skin biopsy. CONCLUSION: Isolated involvement of pinna in a patient without lesions in other body parts is an unusual initial presentation of leprosy. However, leprosy should be kept as a rare differential diagnosis of isolated lesions on the ear in patients not responding to conventional treatment.